Assessment of domestic violence and its associated factors among ever-married reproductive-age women in Cameroon: a cross-sectional survey - Bezawit Mulat; Menen Tsegaw; Dagmawi Chilot; Kegnie Shitu (BMC, 2022)
Abstract Background Domestic violence (DV) against women is a global issue that affects women in all countries and is a significant contributor to their poor health. Women who have experienced DV, in particular, suffer from the gynecological, nervous system, and stress-related issues. Despite such devastating implications, there is a paucity of data on the prevalence of DV and its associated factors among married reproductive-age women in Cameroon. Method The data were analyzed by using STATA version 14 from a demographic and health survey conducted in Cameroon in 2018. Both bivariable and multivariable logistic regression analyses were done. Statistical significance was determined using a p-value of less than 0.05 and a 95% confidence range. Result A total of 4,903 ever-married women were included in the study. The mean age ± standard deviation, of the participants was 31.3 (± 8.4) years with an age range of 15-49 years. The prevalence of DV among ever-married Cameroonian women was 30.5% with 95%CI (29.3%, 31.8%). Women's educational attainment (higher educational level) (AOR = 0.58, 95% CI (0.37, 0.92), p value = 0.02), Husband's educational level (husbands who attended primary educational level (AOR = 1.30, 95% CI (1.01, 1.68), p value = 0.04), a woman who had media exposure regarding DV ( AOR = 0.83, 95% CI (0.0, 0.99), p value = 0.04), a woman whose husband drinks alcohol (AOR = 3.00, 95% CI (2.56, 3.53), p value < 0.001), and the region where the women reside (center without Yaoundé (AOR = 2.48, 95% CI (1.75, 3.52), p value < 0.001), west (AOR = 1.49, 95% CI (1.05, 2.11), p value = 0.02), South (AOR = 1.89, 95% CI (1.31, 2.72), p-value = 0.001), and Yaoundé (AOR = 1.65. 95% CI (1.14, 2.39), p value = 0.009) were factors that were significantly associated to DV committed by a husband in the previous 12 months against ever-married women. Conclusion The present study revealed that the prevalence of DV among ever-married women in Cameroon is high. Women's educational level, husband's educational level, husband's alcohol drinking status, women's exposure to mass-media about DV, and the region where the woman resides in the country were factors significantly associated with DV.